2007
DOI: 10.4103/0022-3859.30334
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis as a distinct disease entity

Abstract: Psoriatic arthritis (PsA) is a chronic systemic inflammatory disease characterized by joint inflammation associated with cutaneous psoriasis. For many years, the amount of attention directed to PsA had been less than that for various other arthropathies. With the advances in understanding its pathogensis, it is now recognized as a distinct disease entity with characteristic features. Psoriatic arthritis has a greater tendency towards asymmetric oligoarticular involvement, distal interphalangeal involvement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
0
24
1
2
Order By: Relevance
“…It most commonly affects the distal joints in the hands and feet, but can also cause inflammation, swelling and pain in larger joints, including the knees, elbows, hips and the spine. PsA presents with a wide spectrum of clinical symptoms including morning stiffness, dactylitis, distal interphalangeal (DIP) joint disease, enthesitis, actively inflamed joints, and joint deformities 18,23 . PsA was previously considered a mild disease.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…It most commonly affects the distal joints in the hands and feet, but can also cause inflammation, swelling and pain in larger joints, including the knees, elbows, hips and the spine. PsA presents with a wide spectrum of clinical symptoms including morning stiffness, dactylitis, distal interphalangeal (DIP) joint disease, enthesitis, actively inflamed joints, and joint deformities 18,23 . PsA was previously considered a mild disease.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…Different studies have shown that up to 30% of patients with psoriasis have psoriatic arthritis of which 70-80% have nail involvement. [1011] Therefore, being a dermatologist, one should look for early signs and symptoms of psoriatic arthritis in a patient with nail psoriasis in order to avoid progressive joint damage. [11121314]…”
Section: Introductionmentioning
confidence: 99%
“…The clinical spectrum is very heterogeneous depending on involvement of the nail bed, matrix, or folds, and includes pitting, grooving, and stippling, as well as discoloration, leukonychia, and onychodystrophy ranging to onycholysis 4. Combined nail matrix and nail bed psoriasis can develop in cases of very severe inflammation, a possible consequence of which is the formation of only parakeratotic, crumbly material by the matrix and bed, a condition referred to as “psoriatic crumbly nail” 5. This finding constitutes a risk factor for secondary mycotic infections, which can occur in up to 27% of psoriasis patients, and calls for more detailed diagnostic tests and therapy adapted to the findings 6.…”
Section: Introductionmentioning
confidence: 99%